Dispositional mindfulness profiles and psychological symptoms: a latent profile analysis - Fereshteh Mehrabi; Fereshteh Mehrabi; Shadi Beshai; Shadi Beshai (Frontiers in Psychology)
ObjectivesIn this study, we aimed to (1) examine profiles of mindfulness using the short form of the FFMQ (FFMQ-SF), (2) identify the demographic predictor (i.e., sex) of mindfulness profile membership, and (3) examine associations of mindfulness profiles with psychological outcomes (i.e., anxiety and depressive symptoms).MethodsThis cross-sectional study included 604 individuals recruited from Amazon’s Mechanical Turk platform (MTurk). We performed latent profile analyses (LPA) to explore the individual profiles based on scores on dispositional mindfulness facets. Dispositional mindfulness was measured using the Five-Facet Mindfulness Questionnaire-Short Form (FFMQ-SF). Depression was assessed using the Patient Health Questionnaire-9 (PHQ-9). Anxiety symptoms were measured by the Generalized Anxiety Disorder Scale (GAD-7).ResultsWe identified three mindfulness profiles including, Judgmentally Describing, Low Mindfulness, and Non-Judgmentally Describing. Participants in the Low Mindfulness group were more likely to be women compared to the other two profiles (Judgmentally Describing and Non-Judgmentally Describing groups). Participants in the Low Mindfulness group had the highest levels of anxiety and depressive symptoms, whereas individuals in the Non-Judgementally Describing group had the lowest levels of depression and anxiety.ConclusionIn the present study, we demonstrated three profiles of the FFMQ-SF, which had differential relationships with anxiety and depressive symptoms. Consideration of such profiles may help clinicians to develop more fine-tuned mindfulness-based psychological interventions.